1986
DOI: 10.1200/jco.1986.4.12.1835
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and pharmacologic study of hexamethylene bisacetamide in patients with advanced cancer.

Abstract: Hexamethylene bisacetamide (HMBA, NSC 95580) has been demonstrated to be the most effective of the known and studied polar-planar compounds at inducing differentiation in a wide variety of leukemic and nonleukemic cell lines. Although HMBA demonstrated no antineoplastic activity in preclinical testing, it was selected for clinical development on the basis of its potent differentiating capabilities in vitro. In this phase I study, HMBA was administered as a continuous five-day infusion every 3 weeks to patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The clinically tested chemotherapeutic hexamethylene bisacetamide (HMBA) [32] has been demonstrated to alleviate this transcriptional block by promoting the localization of P-TEFb to the LTR to enhance viral transcriptional elongation [3335]. We hypothesized that any drug synergy observed between TNF and HMBA would not show a strong dependence on the chromatin environment of the latent viral integration because P-TEFb levels should be similar across Jurkat cells regardless of the viral integration site.…”
Section: Resultsmentioning
confidence: 99%
“…The clinically tested chemotherapeutic hexamethylene bisacetamide (HMBA) [32] has been demonstrated to alleviate this transcriptional block by promoting the localization of P-TEFb to the LTR to enhance viral transcriptional elongation [3335]. We hypothesized that any drug synergy observed between TNF and HMBA would not show a strong dependence on the chromatin environment of the latent viral integration because P-TEFb levels should be similar across Jurkat cells regardless of the viral integration site.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, experimentation showed that HMBA also induced terminal differentiation in a variety of leukemic cell lines [2, 10]. Based on these findings, HMBA was studied in several Phase I and Phase II clinical trials for the treatment of myelodysplastic syndrome (MDS), acute myelogenous leukemia (AML), general advanced cancer, and solid tumors [3-9]. However, serious side effects of HMBA, such as thrombocytopenia, limited the dose escalation and prevented sufficient plasma concentrations to be realized for its terminal differentiating potential.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, the published analytical methods for the measurement of HMBA in plasma and urine are LC-UV and GC-N/P based methods, which have lower limits of quantitation (LLOQs) of 1.00 μg/mL and 2.00 μg/mL, respectively [17, 18]. These and other methods have been applied to several high-dose HMBA Phase I and II clinical trials [3-9, 19, 20], but the LLOQs of these methods are not sufficient for the measurement of HMBA in the majority of biological samples for breast cancer study with concentrations less than 1.00 μg/mL. This paper describes, for the first time, the development and validation of an LC-MS/MS method for the quantitative measurement of HMBA in both mouse and human plasma with an LLOQ of 0.500 ng/mL and a linear calibration range up to 100 ng/mL.…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro studies provided a basis for evaluating the potential of HMBA as a cytodifferentiation agent in the treatment of human cancers (26). Several phase I clinical trials with HMBA have been completed (27)(28)(29)(30)(31)(32). Evidence has been reported that this compound can induce a therapeutic response in patients with cancer (31,32).…”
mentioning
confidence: 99%